Análise comparativa da coordenação motora de crianças de 4 a 6 anos, nascidas pré-termo, associada a fatores sócio-ambientais - Capelini, Juliana Cerqueira (2011)
The aim of this study was to analyze the motor coordination and social-environmental factors of children aging 4 to 6 years old, who were born preterm. 42 children were evaluated, 21 preterm and 21 full-term. The instruments used were the M-ABC battery, an interview with parents / guardians and an ABEP socioeconomic questionnaire. This cross-sectional research has examined the difference between these factors and the association in order to reveal new information for knowledge, education and development of these children. In the characterization of the groups, most of the numerical variables have not showed normal distribution at the Shapiro-Wilk test, so the nonparametric Mann-Whitney test was used to test the differences. For the categorical variables we used the chi-square test, verifying the possible associations. The adopted level of significance was 5%. It was found, in general, that children born preterm had lower motor performance (TDC) in the M-ABC (p = 0.007) when compared to the motor performance of children born full-term. There was also statistically significant association (p = 0.038) between gestational age and the classification of ABEP, with 76.2% of individuals born preterm classified in class C. It was found that in addition to prematurity, the socioeconomic class influenced the results, so, it is believed that these children have fewer motor opportunities driven, which would be enhanced as they grow. These results, as well as other relevant studies, point to the importance of public policies for postnatal care at least until school age to infants, especially in relation to motor stimulation.